Lexical and Contextual Meanings in Coldplay's Everyday Life Album - Meazzazera Chemafachri Alfarizzi; Yenti; Norra Erisha (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2026)
This study investigates lexical and contextual meanings in selected songs from Coldplay's Everyday Life (2019) album. The research aims to identify the lexical meanings and contextual meanings contained in the song lyrics and to explain how these meanings contribute to the interpretation of the songs. This study employed a descriptive qualitative method. The data were collected from seven selected songs, namely Daddy, Church, Arabesque, Trouble in Town, Broken, When I Need a Friend, and WOTW/POTP. The lyrics were obtained from official sources and analyzed using semantic theories proposed by Geoffrey Leech, John Lyons, and Abdul Chaer. The findings reveal that the songs contain 66 lexical meanings and 66 contextual meanings. Lexical meanings represent the dictionary meanings of words and expressions, while contextual meanings emerge from emotional, social, cultural, and spiritual contexts embedded in the lyrics. The analysis demonstrates that Coldplay employs language not only to convey literal messages but also to express deeper themes such as love, loss, hope, faith, humanity, and social criticism. The study concludes that understanding both lexical and contextual meanings is essential for interpreting song lyrics comprehensively and uncovering the intended messages behind artistic language